2001
DOI: 10.1046/j.1365-8711.2001.04596.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of star formation in RCW 106 using far-infrared observations

Abstract: High‐resolution far‐infrared observations of a large area of the star‐forming complex RCW 106 obtained using the TIFR 1‐m balloon‐borne telescope are presented. Intensity maps have been obtained simultaneously in two bands centred around 150 and 210 μm. Intensity maps have also been obtained in the four IRAS bands using HIRES‐processed IRAS data. From the 150‐ and 210‐μm maps, reliable maps of dust temperature and optical depth have been generated. The star formation in this complex has occurred in five linear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 45 publications
0
42
1
Order By: Relevance
“…Typical outflow masses are 10 to 40 M⊙in each lobe, compared to core masses of order Table 10. IR source fluxes in Jy measured with MSX, IRAS, TIFR balloon-borne telescope (Karnik et al 2001) and SEST/SIMBA (Mookerjea et al 2004). The second row for G333.6-0.2 is for fluxes taken within a 3 ′ aperture.…”
Section: Discussionmentioning
confidence: 99%
“…Typical outflow masses are 10 to 40 M⊙in each lobe, compared to core masses of order Table 10. IR source fluxes in Jy measured with MSX, IRAS, TIFR balloon-borne telescope (Karnik et al 2001) and SEST/SIMBA (Mookerjea et al 2004). The second row for G333.6-0.2 is for fluxes taken within a 3 ′ aperture.…”
Section: Discussionmentioning
confidence: 99%
“…There exist a large number of molecular condensations which are only bright in the millimeter wavelengths and have no IR associations. MMS54 has no MSX or IRAS associations but was detected in the FIR by Karnik et al (2001) and has an associated methanol maser; it is a strong candidate for a star forming region at a very early stage of evolution. The continuum emission has been resolved in to Gaussian and arbitrary-shaped clumps using the two independent structure decomposition tools gaussclumps and clumpfind respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The case of MMS54 is an apt example. While its fainter companion MMS57 has an MSX counterpart, the stronger millimeter source MMS54 has no IRAS or MSX associations, but was detected both at 150 and 210 µm by Karnik et al (2001) and has an associated methanol maser (Ellingsen et al 1996, observed with an angular resolution of 4 ). This definitely suggests that MMS54 shows early signs of massive star formation and demands further high angular resolution sub-mm dust continuum observations to characterize its nature.…”
Section: Figmentioning
confidence: 98%
See 2 more Smart Citations